Juridical Review Of Child Victims Of Cyberbullying Through Social Media Reviewed From The Perspective Of Criminal Responsibility - Balimeita Betania Nasaretta Tarigan (LAWYER: Jurnal Hukum, 2024)
Children as part of the young generation are one of the potential human resources and as successors to the ideals of the nation's struggle in the present and future. Children have a strategic role and have special characteristics and characteristics, so they require guidance and protection in order to ensure balanced physical, mental and social growth and development. The aim of the research is to determine the juridical influence of child victims of cyberbullying via social media from a criminal liability perspective. This research uses normative juridical research methods. Normative legal research is legal research that examines written law from various aspects, namely aspects of theory, history, philosophy, comparison, structure and composition, scope of material, and consistency. The conclusion in this research is that the legal basis for the criminal act of cyber bullying is Article 315, because the criminal act of cyber bullying fulfills both the subjective and objective elements contained in Article 315 of the Criminal Code. The regulation of criminal acts of cyber bullying outside the Criminal Code is contained in Article 27 Paragraph (3) of the ITE Law because this article explains about insults carried out via computer or electronic media which is in accordance with the act of cyber bullying which is an insult through cyberspace. In realizing legal justice for society, especially in cases of criminal acts of insults in cyberspace (cyber bullying), it would be better for the government and law enforcement officials to expand further and make specific regulations in the Criminal Code. There are clear arrangements to make it easier to prove crimes if there are cases like the ones above.